Contamination of Dhanmondi and Gulshan Lake Waters with Some Metals and Inorganic Pollutants (Journal of Bangladesh Academy of Sciences, 2010)
Air, soil and water are continuously being polluted by the anthropogenic activities andsometimes by natural calamities. Among the three components, water pollution perhaps is the mostimportant one. The contamination of water resources and biota is of major concern especially inindustrialized countries because of the discharge of toxic, persistent and bio-accumulativesubstances from various sources. Household wastes dumped by the city dwellers contribute also toa great extent to the pollution of urban areas.Key words: Contamination; Lake waters; Metals; Inorganic pollutantsDOI: 10.3329/jbas.v34i1.5495Journal of Bangladesh Academy of Sciences, Vol.34, No.1, 89-93, 2010